Governança pública aplicada à gestão da propriedade intelectual: um estudo em núcleos de inovação tecnológica de universidades públicas - Ribeiro, Patricia Gava (2019)
The university constitutes a fundamental institution of knowledge-based societies, through teaching, research and extension. In this way, increasingly the university – productive sector interaction shows an elevated importance to stimulate economic development. This interaction happens specially regarding the technology transfer activity, which occurs through a strong and competent intellectual property protection. Thus, after the promulgation of Act n° 10.973/2004, better known as the Innovation Act, arose the mandatory establishment of Technological Innovation Centers (called NITs) in the Science and Technology Institutions (called ICTs), these being the bodies responsible for the management of innovation and protection of intellectual property (called as PI) in universities. At the same time, public governance has been gaining increasing highlight in the world scenario, considering that its good practices are essential for a efficient management, as well as for the development of society as a whole. In this sense, the present study aimed to verify, together with NIT managers, how public governance practices are adopted to carry out the management of intellectual property. To reach the proposed objective, a bibliographic research was used to construct the theoretical reference, besides an instrument of data collection (questionnaire). In addition, some data were collected in the institutional portals of the participating universities of the study, with the purpose of provide support and consolidate the data collected through the questionnaire. The research can be classified as applied, with na exploratory-descriptive objective and qualitative/quantitative approach. Furthermore, as a case study, was opted to conduct a research with the Innovation Agency (AGINT) of the Federal Technological University of Paraná (UTFPR). Regarding the initial hypothesis suggested in the study, that public governance constitutes an essential and indispensable aspect for the intellectual property to be managed by the NITs of public universities in na efficient manner, aiming at the transfer of technology to the private sector, the research proved that in practice this does not occur. The reached results from the answers of 30 NITs from South and Southern Regions, according to the qualitative and quantitative approaches, showed that there is not a correlation between practices of public governance and results of PI in NITs.